A new species of Ituglanis Costa & Bockmann, 1993 (Siluriformes: Trichomycteridae) from Rio Ribeira de Iguape and upper Rio Tietê basins, southeastern Brazil - Mendonça, Marina Barreira; Oyakawa, Osvaldo Takeshi; Wosiacki, Wolmar Benjamin (Zootaxa, 2018)
Ituglanis amphipotamus, new species, is distinguished from all congeners by the combination of the following characters: anterior cranial fontanel present, i,5 pectoral-fin rays, nasal canal and antorbital segment of infraorbital canal absent, five or six pairs of ribs, 39 post-Weberian vertebrae. It can be further distinguished from the sympatric I. proops by the size of the interopercular patch of odontodes. The new species is described from the Rio Ribeira de Iguape and the upper Rio Tietê basins in the southeastern region of Brazil. Comments on the biogeography of the new taxa and putative relationships with its congeners are presented. [Zoobank: urn:lsid:zoobank.org:act:AC2F3365-92C0-4444-AC89-9546365158EC]